Stable states in soil chemistry persist in eucalypt woodland restorations. Issue 1 (11th November 2018) - Macdonald, Stuart; Bailey, Tanya; Hunt, Mark; Davidson, Neil; Jordan, Greg
Abstract: Aim: To assess whether restoration of dry eucalypt‐dominated plant communities on ex‐pasture sites is constrained by soil characteristics. Location: Central Tasmania, Australia. Methods: We use nutrient status to test recovery trajectories of soils within eucalypt woodland restorations established on ex‐pasture sites. Eucalyptus trees within these sites have been successfully established but understorey plant communities have had negligible recovery. Soils from restoration sites, aged from 3 to 22 years, were contrasted with those from two reference ecotypes: established pastures and native eucalypt woodlands presumed to be similar to that originally replaced by the pastures. We hypothesized that (a) total soil carbon to nitrogen ratios (C:N) would be substantially higher in forest soils than in pasture soils; (b) soil nutrient levels would be lower in forest sites than within pasture sites; and (c) if restoration soils were recovering they should fit between these continuums according to age of planting. Results: Woodland and pasture reference soils were highly constrained in soil C:N and conformed to expectations. However, ex‐pasture restoration sites retained the characteristically low C:N and high nutrient levels of pasture soils, in particular total N. They also failed to demonstrate a transformational effect with age of planting. Conclusions: The results suggest that both restoration interventions and natural processes had not sufficiently disrupted existing below‐ground systems within the given time frame. Such an intractable stable state within the soil system highlights the need within restoration practice for an increased emphasis on soil ecological transformation. Improving and implementing practices aimed at driving soil change may assist a timelier reassembly of complex native ecosystems. This study also shows that soil C:N ratios may provide a cheap and simple means of identifying soil constraints on restoration. Abstract : Historical legacies on ex‐agricultural sites can pose considerable constraints to the re‐assembly of native vegetation communities. In eucalypt forest restorations we demonstrate the intractability of total soil carbon to nitrogen ratios. Soil chemistry remained consistent with previous pasture status and distinct from that of native forests. We suggest these findings support the need for increased emphasis on soil focused intervention.